Kesulitan Siswa dalam Memahami Pelajaran Matematika dan Cara Mengatasinya - Dani Pratama Effendy; Adrias Adrias; Aissy Putri Zulkarnaini (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Mathematics plays a crucial role in everyday life, as it enhances students' abilities to absorb lessons more effectively and develop rational, critical, logical, analytical, and systematic thinking. This study employs the literature review method, which involves gathering relevant information from various sources to support the research topic. The author collects references from articles and journals using Google Scholar, an open-access database that simplifies the process of locating topic-specific materials. Difficulties faced by students in learning mathematics are not always due to a lack of mathematical knowledge. They may stem from other issues such as memory problems, difficulty in recalling mathematical problems, weak calculation skills, confusion with operational signs, or reversing numbers. Students with learning disabilities may particularly struggle with both mathematical reasoning and basic computation. Furthermore, mathematical learning difficulties are also associated with cognitive challenges, such as solving complex word problems and understanding numerical concepts. These learning difficulties often result from internal and external factors that hinder the brain’s ability to process, analyze, and retain mathematical information effectively.